2004
DOI: 10.1021/ja049634m
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Conserved P9-G10.1 Metal-Binding Motif in Hammerhead Ribozymes with an Extra Nucleotide Inserted between A9 and G10.1 Residues

Abstract: Hammerhead ribozymes (Rz) have catalytically important tandem G:A pairs in the core region, and we recently demonstrated that the P9-G10.1 motif (a sheared-type G:A pair with a guanine residue on the 3' side of the adenine residue) with several flanking base pairs is sufficient for capture of divalent cations, such as Mg(2+) and Cd(2+) ions that are important to maintain full activities (Tanaka et al. J. Am. Chem. Soc. 2002, 124, 4595-4601; Tanaka et al. J. Am. Chem. Soc. 2004, 126, 744-752). We also found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…While the catalytic cores of nHH1 to nHH9 are not identical, the observed sequence variations at position 7 (U, G, or A) are not expected to significantly modify rates based on experiments with minimal hammerheads (43). A residue that is likely to be responsible for some of the catalytic diversity is the "bulged" nucleotide positioned between A9 and G10 (9), which substantially enhances cleavage of minimal hammerheads (10,44) and is present in the three fastest hammerheads studied here (nHH3, nHH5 and nHH8). Another source of catalytic diversity could be the varying sequence at the base pairs 1.1-1.2 and 2.1-2.2 which can modify cleavage rates in minimal hammerheads about 10-fold (45).…”
Section: Discussionmentioning
confidence: 99%
“…While the catalytic cores of nHH1 to nHH9 are not identical, the observed sequence variations at position 7 (U, G, or A) are not expected to significantly modify rates based on experiments with minimal hammerheads (43). A residue that is likely to be responsible for some of the catalytic diversity is the "bulged" nucleotide positioned between A9 and G10 (9), which substantially enhances cleavage of minimal hammerheads (10,44) and is present in the three fastest hammerheads studied here (nHH3, nHH5 and nHH8). Another source of catalytic diversity could be the varying sequence at the base pairs 1.1-1.2 and 2.1-2.2 which can modify cleavage rates in minimal hammerheads about 10-fold (45).…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of the structure of hammerhead ribozymes and of the conformational changes caused by interactions with Mg 2+ ions have indicated that two major conformational changes occur: the formation of domain II, which is followed by the formation of domain I, as shown in Figure 1C (38,45,48,50,54). The formation of domain II results in coaxial stacking of helices II and III, induced by the binding of a higheraffinity Mg 2+ ion(s) to P9 phosphate and N7 of G 10.1 (P9/ G10.1) of the ribozyme-substrate complex (38,45,48,50,(54)(55)(56)(57)(58). The second transition is the formation of the catalytic domain with movement of stem I toward stem II, which is induced by the binding of a lower-affinity Mg 2+ ion(s).…”
Section: The Dependence Of the Activity Of The Hammerhead Ribozyme Onmentioning
confidence: 99%
“…The conserved central bases, with few exceptions, are essential for ribozyme's catalytic activity (28). In terms of the structure (31)(32)(33)(34)(35)(36) and in terms of the cleavage chemistrykinetic studies (37)(38)(39), folding studies (29,(40)(41)(42)(43)(44), effects of ion binding and rescue (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55), elemental substitution at the cleavage site (49,56), cross-linking (28), effects of protonation and proton transfer (57)(58)(59)(60), single molecule studies (42,(61)(62)(63), phosphoryl transfer mechanism (37,(64)(65)(66)(67)(68)(69)(70), alternative reaction mechanisms (71,72...…”
Section: Introductionmentioning
confidence: 99%